(untitled) (AYUSHDHARA, 2016)
The detail concept of ‘Chardi’ was compiled & elaborated in this section from Ayurveda & modern view. The present study includes a sample size of 60 children in and around Institute area. Haritaki churna” described in Charak, is well & safely practiced drug among many Vaidyas by proving its efficacy on Chardi. As mentioned before, Research works have covered the diseases of Annavaha srotas like that of Pravahika, Krimi, Atisara etc. But no consideration was given to the aspect of Chardi or such complaints with nature of reoccurrence. The total over all therapy showed that, 28.33 % showed no improvement, 51.66 % showed mild improvement, 18.33 % showed moderate improvement and 1.66 % showed marked improvement. There is progressive improvement occur in number of Vomiting episodes and Vibandha because Haritaki churna have Vatanulomana property which helps in decreasing Pratiloma gati of vitiated Vata and relieved vomiting episodes also help in bowel motility and relieved of constipation. Mild to Moderate improvement occur in Udarashoola, Skin fold, Capillary refill and in Urine output. Probably by correction of dehydration of body due to decrease in episodes of vomiting and also due to Haritaki is having Rasayana property. No improvement in Trushna, Mental status, Extremities, Characteristics of pulses.